Clinical and laboratory data in pediatric autoimmune hepatitis: study from referral center in Iran - Haghighat, Mahmoud (2020)
Background: Autoimmune hepatitis (AIH) is an auto-inflammatory liver disease of children and adults, affecting patients of any age, sex, race or ethnicity, with more prevalence in females. Objective: The aim of this study was to evaluate clinical manifestation, laboratory findings, and outcome of children with autoimmune hepatitis. Materials and methods: We evaluated 86 patients treated and followed with final diagnosis of AIH between years 2010 to 2018. Physical findings (including jaundice, hepatomegaly, splenomegaly and encephalopathy), liver enzymes, liver histology and autoantibodies (including ANA, Anti LKM-1 and ASMA) were extracted from medical files. Then the patients were followed for their final outcome (including response to medical treatment or successful treatment withdrawal, liver transplantation or death). Results: Among 86 patients with AIH with mean age 9.10±4.36 years old, 66.27% were females. Jaundice (75.6%) and hepatomegaly (46.5%) were the most frequent physical findings, followed by splenomegaly (32.6%) and encephalopathy (17.4%). Aminotransferases including AST and ALT were elevated at least 3 times more than upper limit of normal in most of the patients (61.6% and 55.81%, respectively). Autoantibodies were available in 53 of 86 patients, 24.5% had AIH-1, 3.8% had AIH-II and 67.9% were seronegative. Medical treatment including prednisolone and azathioprine was started for patients, 53 of 86 cases (61.6%) had remission and 11 of 86 (13.7%) tolerated medication withdrawal successfully. Among all cases, 26 (30.2%) patients needed liver transplantation. Mortality rate was 9 among dice and hepatomegaly was the most frequent clinical findings. Mortality rate was 10.5%.